A serosurvey for bovine respirovirus 3 in Turkish domestic ruminants: The first comparison study of A and C genotypes - Muftuoglu, Bahadir; Kurucay, Hanne Nur; Elhag, Ahmed Eisa; Yildirim, Serdar; Cicek-Yildiz, Yasemin; Tamer, Cuneyt; Yazici, Zafer (Wiley, 2021)
Bovine parainfluenza virus-3 (BPIV-3), also known as bovine respirovirus 3, causes serious respiratory infection in ungulates, often involving other pathogens, such as viruses, bacteria and mycoplasmas. In this study, we evaluated antibody titers against virus genotypes A (BPIV-3a) and C (BPIV-3c). We conducted a serological survey and comparison analysis of archived serum samples from small and large ruminants reared in four Turkish provinces. A total of 1,307 samples, consisting of sheep (n = 444), cattle (n = 402), water buffalo (n = 261) and goat (n = 200) sera, were randomly selected from stock samples collected between 2015 and 2019 and screened by standard virus neutralisation assay. We found that 49.9% (653/1307) of all samples were positive for neutralising antibody titers. Goats had the highest titer, with total seropositivity of 63% (126/200), followed in descending order by cattle, sheep and water buffalo at 56.2% (226/402), 32.2% (143/444) and 26% (68/261) total seropositivity, respectively. BPIV-3c had the highest neutralising antibody rate at 34.3% (448/1307), whereas BPIV-3a had a 24.3% (317/1307) seropositivity rate. Neutralising antibody titers for positive samples ranged between 1/4 and 1/512 per the SN50 test. Seropositivity rates ranged from a low of 8.9% to a high of 18.3%. Our study was the first to compare antibody seroprevalence for two BPIV-3 genotypes in small and large domestic ruminants, which were shown to be more commonly exposed to BPIV-3c than BPIV-3a. This finding could have significant implications as current vaccines mainly use the BPIV-3a genotype. Further research can determine if current vaccines protect against different BPIV-3 virus genotypes.
Keywords: BPIV-3; genotype A; genotype C; neutralised antibodies; ruminants